Problems of improving the national legislation on labor protection - K. Yu. Melnyk (Law and Safety)
The article examines the norms of the current and future national legislation in the field of labor protection and the norms of the legislation of the European Union regarding the safety and health of workers at work. It is noted that the national legislation in the field of labor protection today is characterized by certain obsolescence and inconsistency with the normative documents of the European Union in the relevant field. An analysis of the norms of the drafts of the Law of Ukraine “On Safety and Health of Workers at Work” and the Law of Ukraine “On Amendments to Certain Legislative Acts of Ukraine Regarding Liability for Violation of the Requirements of the Law on Safety and Health of Workers at Work” prepared by the Cabinet of Ministers of Ukraine is being carried out.